The observation on the inhibition of anti-inflammatory mediator of the tomato leaves extract - Amid, Azura; Semail, Sulawati; Jamal, Parveen (IIUM Press, 2011)
The leaves of tomato plant that contained several active compound including alkaloid, steroid and f1avanoid has been used for treatmcnt of varicty of diseases included ami-cancer, amioJ< idant and anti-gout. However, thcre arc no studies on the anti-inflammation from thc action of tomatO leav~. In this study, the inhibitory of inflammation of Solanum {ywpe,skum was investigated by observing the Prostaglandin El (rGE!) production with LPS-stimulated murine maffOphage cells RAW264.7. The leavcs CJ<traCI of So/anum ~I"CQpe'siclim were tested for antiinflammatory effcct against lipopolysalX'haride (LPS)- induced rGEl according to a instructions of the manufacturer providcd in commercially available PGE! enl}me immunometric assay kit (Cayman CO.. Ann Arbor, MI, USA). Then, the c,)Ocentrations of rGE! were determined using commercial ELISA kit and the inhibition of PGE! was calculated. Results showed that the tomato leaves extract inhibited the productions of inflammatory mcdiators (1'<.iE!) which plays a central role in the anti-inflammatory activity. At the high~t concentration (100 ~glml) of tomatO leaves extract tested, the PGE, production was reduced 37.41% compared to the untreated. Hence. these present study may suppon that the leaves of SolanwlI (l'cof'f'l"Sicli/ll extract potentially in treatment of inflammatory-related disease through the inhibition of PGE! releast':s.